Caminhos, dificuldades e acertos da escola regular na inclusão de pessoas com síndrome de Down: relato de pais - Vieira, Camila de Velasco e (2021)
This study aimed to analyze the inclusion of people with Down Syndrome in regular school, and as specific objectives: to verify which are the biggest difficulties found in the process of school inclusion; identify which pedagogical practices were successful for people with Down Syndrome during inclusion; understand the role of an institution specialized in the educational and social inclusion of people with Down Syndrome; discuss the family as a space for social and educacional inclusion. It is a qualitative research with field research, through the life of parents’history of people with Down Syndrome. It’s guided by a questionnaire, which sought to learn about the inclusion / exclusion process of their children. Ten adolescents/adults’parents participated in this research with Down Syndrome who are parts of the Down Syndrome Association of Goias. As a product of this study, with the title: life story of parents of people with down syndrome: School inclusion and make an E-book was elaborated with these life storiesforthe training of teachers and professionals of the regularschool,seeking to favor more inclusive pedagogical practices in regular schools. The results indicated that the disastrous experiences were related to: lack of support teacher, exclusion from festive moments, lack of knowledge about characteristics and cognitive process, prejudice and discrimination, lack of affection and welcoming, large classes, segregation, lack of appropriate pedagogy for learning and literacy, among others. The successful pedagogical practices indicated as positive the presence of: planning of pedagogical practices, good relationship with colleagues, welcoming and affection, ample space and with nature, respect for learning time, knowledge, empathy, parental participation, among others. It was also observed the great importance of specialized institutions and the family in educational and social inclusion.Finally, the result of this process will contribute to the change of thinking in relation to people with DS, for the construction of pedagogical measures of teachings and concepts based on the reality of these people.